Westonci.ca is the premier destination for reliable answers to your questions, brought to you by a community of experts. Discover solutions to your questions from experienced professionals across multiple fields on our comprehensive Q&A platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.

3 ( 4d + 1 ) - 9d = 6 - 2d


Sagot :

3(4d+1)-9d=6-2d
12d+3-9d=6-2d
3d+3=6-2d
5d=3 /:5
d=3/5

Answer:

d=3/5

Step-by-step explanation:

3 ( 4d + 1 ) - 9d = 6 - 2d

12d + 3 - 9d = 6 - 2d

12d - 9d + 2d = 6 - 3

5d = 3

d = 3/5

d = 0.6